Agro-Food Supply Chain Risk Assessment: A Review Based on Technique and Approach - Daniel Bunga Paillin; Machfud Machfud; Hartrisari Hardjomidjojo; Muhammad Romli (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Risk assessment in agro-food supply chains is crucial in managing the complexity and uncertainty associated with food product production, distribution, and consumption. This study aims to classify risks and mapping techniques or approaches used in risk assessment of agro-food product supply chains. Mapping technique or approaches to risk assessment of agro-food supply chains was carried out based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) framework, which consists of several stages of identification, screening eligibility, and inclusion, resulting in a total of 72 relevant journal articles. They were selected from 58 different journals with high-impact factors and rankings. The literature review results show that agro-food's supply chain risk classification has much to do with risk assessment: macro-level risk, operational risk outside the company, and internal risk. Furthermore, the most studied agro-food products are general food (44%), horticultural products (28%), meat products (11%), dairy products (10%), fishery products (6%) and bread products (1%). The techniques and approaches most widely used in assessing the risk of the agro-food supply chain are semi-quantitative (49.3%), quantitative (31.5%), mixed (12.3%), and qualitative (6.9%). A better knowledge of the topic being addressed in the research community is sped up by identifying these techniques and approaches since the literature on supply chain risk management for agro-food is voluminous, complicated, and challenging to grasp.